“COVID-19” Pandemic: Rethinking Defence Spending in Bulgaria - Dimitrov, Atanas (UNWE Yearbook, 2021)
This paper investigates defence spending in Bulgaria in the context of the COVID-19 pandemic. It analyses military expenditures on both regional and national scales and tries to compare the post-financial and economic crisis period of the first decade of the 21st century to the current pandemic situation. The paper argues that it is unlikely that the ever evolving threat landscape will lead to a significant decrease in defence spending, while requiring its rethinking in Bulgaria with a focus on investments in technologies and related activities. Due to the ongoing pandemic and the fact that relatively little time has passed since its emergence, part of the conclusions drawn are primarily prospective in nature.
Keywords: Defence spending; Pandemic; COVID-19; Military expenditures; Defence budget